2003
DOI: 10.1081/al-120023614
|View full text |Cite
|
Sign up to set email alerts
|

Testing the Durability of Polymyxin B Immobilization on a Polymer Showing Antimicrobial Activity: A Novel Approach with the Ion-Step Method

Abstract: A polymyxin B (PMB) modified copolymer of ethyl acrylate and 2hydroxyethyl methacrylate is reported that shows antibacterial activity towards E. coli. The polymer is designed for biosensor interfaces to provide protection against microbial contamination. However, leaching of a biomolecule from its solid support is a well-known problem in immobilization chemistry. It has been proposed that antimicrobial activity results from release of the antibiotic from the polymer matrix, but in the work reported here, bacte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 53 publications
0
5
0
Order By: Relevance
“…This led them to conclude that the elution in solution would be much less than the MIC for PMB. 58 They then determined the antimicrobial efficacy using an optical density measured growth curve lag between inoculated media that was or was not exposed to PMB immobilized glass. The bacteria in the media exposed to PMB glass had a delayed growth curve.…”
Section: F Peptidesmentioning
confidence: 99%
See 1 more Smart Citation
“…This led them to conclude that the elution in solution would be much less than the MIC for PMB. 58 They then determined the antimicrobial efficacy using an optical density measured growth curve lag between inoculated media that was or was not exposed to PMB immobilized glass. The bacteria in the media exposed to PMB glass had a delayed growth curve.…”
Section: F Peptidesmentioning
confidence: 99%
“…8,9 A wide range of antimicrobial agents have been immobilized, including small molecules (e.g., quaternary ammonium silanes), [10][11][12][13][14][15][16][17] quaternary ammonium polymers, [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35] polyamines, [36][37][38][39][40][41][42] chitosan, [43][44][45][46][47][48][49] enzymes, [50][51][52][53][54][55] peptides, and peptide mimetics. [56][57][58]…”
Section: Introductionmentioning
confidence: 99%
“…One of the methods for regulating the pharmacological activity of such drugs is their immobilization on various carriers, which can increase the stability of the molecule, protect it from the effects of certain factors (for example, gastric juice when administered orally), and also provide controlled release into the environment, which allows prolonging the effect. Thus, many examples of successful immobilization of antibiotics, [202,203] enzymes, [204,205] peptides, [206,207] halogen-active, [208][209][210] and peroxide [211] preparations on polymeric carriers of various nature have been described. Low toxicity, large surface area, sorption properties, and the possibility of diffusion of the intercalated anion make SDGs promising containers for various microbiocides instead of hard-to-produce polymer bases.…”
Section: Ldhs As Microbiocidal Agentsmentioning
confidence: 99%
“…The mode of action of antimicrobial peptides includes formation of pores in the cell membrane resulting in the disruption of the membrane potential with eventual lysis of the cell. 67,68 The immobilization of polymyxin B, a cyclic polycationic peptide with a molecular weight of $1,200 on an alkyl acrylate polymer has been reported and the conjugate showed antibacterial action against E. coli. The authors demonstrated that the bioactivity was indeed due to the immobilized AMP and not AMP leached from the polymer.…”
Section: Antimicrobial Peptide-based Coatingsmentioning
confidence: 99%
“…The authors demonstrated that the bioactivity was indeed due to the immobilized AMP and not AMP leached from the polymer. 68 A recent study has reported the immobilization of cathelin LL37, a cryptic antimicrobial peptide obtained by enzymic cleavage of its precursor cathelicidin which is stored in granulocytes. 69 The peptide was covalently immobilized onto a titanium metal surface by means of silanization.…”
Section: Antimicrobial Peptide-based Coatingsmentioning
confidence: 99%